Analysis of Consumer Motivation as a Predictor in Increasing Purchase Intention: An Empirical Study on Organic Product Consumers in Malang City - Ledy Yolanda; Dina Noval Madurani; Muhammad Zakariya Al Anshori (Utan Kayu Publishing, 2025)
This study aims to analyze the role of consumer motivation as a predictor of increasing purchase intention for organic products in Malang City. Specifically, this research will investigate various aspects of consumer motivation, such as utilitarian, hedonic, and ecological motivations, that impact consumer purchasing decisions. Utilitarian motivation focuses on the functional and health benefits of products, while hedonic motivation assesses the emotional satisfaction and positive experiences gained by consumers. On the other hand, ecological motivation relates to consumer awareness of environmental issues and product sustainability. The type of research used is quantitative, with sampling done using the purposive sampling method. The research findings indicate that consumer motivation (utilitarian, hedonic, and ecological) influences their purchase intention toward organic products. This research is expected to contribute to producers in designing more effective marketing strategies by understanding the motivational factors that drive consumers to purchase organic products and to offer vital perspectives on the development of the organic product business in an increasingly competitive market.